2022
DOI: 10.3390/nano12091590
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Octane Moiety Adsorption on H- and Cl-Functionalized Silicon Nanowires

Abstract: Using first-principles calculations based on density functional theory, we investigated the effects of surface functionalization on the energetic and electronic properties of hydrogenated and chlorinated silicon nanowires oriented along the <112> direction. We show that the band structure is strongly influenced by the diameter of the nanowire, while substantial variations in the formation energy are observed by changing the passivation species. We modeled an octane moiety absorption on the (111) and (110… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…The 4 n 2 limit is based on geometrical optics, and it pursues surface decoration of both sides of the thin film in order to increase the optical power in the film. More recently, it was suggested and demonstrated that the 4 n 2 limit can be exceeded if surface decoration with subwavelength structures is employed. Various light trapping mechanisms were identified to produce broadband absorption enhancement of the sun power with surface subwavelength arrays: low optical impedance using arrays of nanocones and black silicon, forward scattering by surface Mie resonators, increase in local density of states, excitations of Bloch modes, light trapping driven by light concentration and the utilization of nanolenses and light funnels, excitations of localized Mie resonances, ,, and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…The 4 n 2 limit is based on geometrical optics, and it pursues surface decoration of both sides of the thin film in order to increase the optical power in the film. More recently, it was suggested and demonstrated that the 4 n 2 limit can be exceeded if surface decoration with subwavelength structures is employed. Various light trapping mechanisms were identified to produce broadband absorption enhancement of the sun power with surface subwavelength arrays: low optical impedance using arrays of nanocones and black silicon, forward scattering by surface Mie resonators, increase in local density of states, excitations of Bloch modes, light trapping driven by light concentration and the utilization of nanolenses and light funnels, excitations of localized Mie resonances, ,, and so forth.…”
Section: Introductionmentioning
confidence: 99%